PISA INTERNATIONAL ASSESSMENT PROGRAM (International journal of artificial intelligence, 2024)
This article examines the PISA international assessment program and the importance of measuring mathematical literacy in it. The PISA program assesses students' ability to apply mathematical knowledge in practice. Also, the results of participation and the weaknesses of the education system in Uzbekistan, including textbooks, teaching methods, and student motivation problems were analyzed. Recommendations for creating practical textbooks, training teachers and increasing the interest of students are given for the development of mathematical literacy.